2015
DOI: 10.1016/j.ccell.2015.01.003
|View full text |Cite|
|
Sign up to set email alerts
|

Recurrent DGCR8, DROSHA, and SIX Homeodomain Mutations in Favorable Histology Wilms Tumors

Abstract: SUMMARY We report the most common single nucleotide substitution/deletion mutations in Favorable Histology Wilms Tumors (FHWT) to occur within SIX1/2 (7% of 534 tumors) and microRNA processing genes (miRNAPG) DGCR8 and DROSHA (15% of 534 tumors). Comprehensive analysis of 77 FHWTs indicates that tumors with SIX1/2 and/or miRNAPG mutations show a pre-induction metanephric mesenchyme gene expression pattern and are significantly associated with both perilobar nephrogenic rests and 11p15 imprinting aberrations. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
179
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(193 citation statements)
references
References 62 publications
13
179
1
Order By: Relevance
“…Alternatively, absolute levels of SIX proteins might be important, and high levels are required for reprogramming and progenitor maintenance. SIX1/2 mutations have recently been associated with Wilms' tumors (Wegert et al, 2015;Walz et al, 2015). These data provide further evidence that the blastemal elements of the tumor reflect the characteristics of the nephron progenitor niche.…”
Section: Six1 Function In Mouse Versus Humansupporting
confidence: 53%
See 1 more Smart Citation
“…Alternatively, absolute levels of SIX proteins might be important, and high levels are required for reprogramming and progenitor maintenance. SIX1/2 mutations have recently been associated with Wilms' tumors (Wegert et al, 2015;Walz et al, 2015). These data provide further evidence that the blastemal elements of the tumor reflect the characteristics of the nephron progenitor niche.…”
Section: Six1 Function In Mouse Versus Humansupporting
confidence: 53%
“…Furthermore, SIX1 and SIX2 mutations have also recently been associated with Wilms' tumor, a pediatric kidney cancer (Wegert et al, 2015;Walz et al, 2015). The tumors are characterized by blastemal, epithelial and stromal elements much like the developing kidney.…”
Section: Introductionmentioning
confidence: 99%
“…These genome-wide mutation analyses also identified low-frequency somatic mutations in epigenetic remodelers SMARCA4 and ARID1A (Rakheja et al 2014). Very recently, mutations in DROSHA and DGCR8 were also identified in exome sequencing studies of highrisk blastemal Wilms' tumors and favorable histology Wilms' tumors (Walz et al 2015). These studies also identified a recurring Q177R missense mutation in both SIX1 and SIX2.…”
Section: Wilms' Tumor Geneticsmentioning
confidence: 82%
“…The recent identification of Q177R missense mutations in SIX1 and SIX2 (Walz et al 2015;Wegert et al 2015) fit neatly with a central role for disturbed control of nephron progenitors in Wilms' tumors. The mutations are somatic, and the majority was found to be in a heterozygous state, in which case wild-type and mutant alleles showed equal expression.…”
Section: Wilms' Tumors and The Control Of Nephron Progenitor Cellsmentioning
confidence: 99%
“…First, a number of childhood cancers occur exclusively in children and adolescents. The genomic landscape of such tumors, including medulloblastoma, neuroblastoma, and Wilms tumors, have been the focus of several recent large-scale research projects, such as the Therapeutically Applicable Research to Generate Effective Treatments (TARGET) (17), the Pediatric Cancer Genome Project (PCGP) (18), the Peds-MiOncoSeq (19) and the BASIC3 (20) projects, and have been found to harbor not only shared but several novel recurrent alterations when compared to the most common genomic alterations seen in adult epithelial malignancies. Such alterations include, in addition to SNVs and indels, a higher preponderance of gene fusions and copy number alterations.…”
Section: Pediatric Somatic Taskforcementioning
confidence: 99%